2008
DOI: 10.1007/s11071-008-9402-y
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of four coupled van der Pol oscillators

Abstract: It is possible that self-excited vibrations in turbomachine blades synchronize due to elastic coupling through the shaft. The synchronization of four coupled van der Pol oscillators is presented here as a simplified model. For quasilinear oscillations, a stability condition is derived from an analysis based on linearizing the original equation around an unperturbed limit cycle and transforming it into Hill's equation. For the nonlinear case, numerical simulations show the existence of two well-defined regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The PLA approximation has been used in previous studies to analyze strong relaxation oscillators, such as the Van der Pol oscillator [12] and the Tyson-Fife model [22]. This has proven to be an effective method for studying relaxation oscillators with different coupling mechanisms including diffusive coupling [12] and delay coupling [23], and in systems with two [12], three [24] and four oscillators [25].…”
Section: Piecewise Linear Approximation a Approximating A Single mentioning
confidence: 99%
“…The PLA approximation has been used in previous studies to analyze strong relaxation oscillators, such as the Van der Pol oscillator [12] and the Tyson-Fife model [22]. This has proven to be an effective method for studying relaxation oscillators with different coupling mechanisms including diffusive coupling [12] and delay coupling [23], and in systems with two [12], three [24] and four oscillators [25].…”
Section: Piecewise Linear Approximation a Approximating A Single mentioning
confidence: 99%
“…The so-called synchronization phenomenon refers to self-adjusting different frequencies of oscillating objects to a unified frequency relying on their internal weak couplings [1,2]. In recent years, the study of synchronization phenomenon is involved in the fields of physics, chemistry, and biology, such as the practical application on complex dynamic network systems [3][4][5], nonlinear coupled chaotic systems [6,7], coupled pendulum system [8][9][10][11][12], and rotor system [1,[13][14][15][16][17][18][19]. Nevertheless, the latter two systems can be categorized as synchronous problem of mechanics system in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a special phenomenon in Since the transition of synchronization can be revealed through dynamical analysis, the synchronization of coupled oscillators was always investigated by studying its dynamics, e.g. [14][15][16]. In [14], Rene investigated different dynamical states of synchronization for a ring of four mutually inertia coupled self-sustained electrical systems which were described by the coupled Rayleigh-Duffing equations.…”
Section: Introductionmentioning
confidence: 99%
“…He also studied the stability properties of periodic solutions and the transition boundaries between different dynamical states by using the Floquet theory. The dynamical behaviors and synchronization of a ring of mutually coupled Van der Pol oscillators were studied by Barrón and Sen [15]. Later on, Perlikowski et al [16] investigated the dynamics of a ring of unidirectionally coupled autonomous Duffing oscillators which indicated that although the individual uncoupled oscillator has one globally stable equilibrium, the response of the coupled oscillators could evolve into periodic, quasi-periodic, and chaotic motions when the coupling strength increases.…”
Section: Introductionmentioning
confidence: 99%